Substituent effects in N-acetylated phenylazopyrazole photoswitches - Tovtik, Radek; Marzin, Dennis; Weigel, Pia; Crespi, Stefano; Simeth, Nadja A. (Beilstein Journal of Organic Chemistry, 2025)
Phenylazopyrazole photoswitches proved to be valuable structural motifs for various applications ranging from materials science to medicine. Despite their potential, their structural diversity is still limited and a larger pool of substitution patterns remains to be systematically investigated. This is paramount as electronic effects play a crucial role in the behavior of photoswitches and a deeper understanding enables their straightforward development for specific applications. In this work, we synthesized novel N-acylpyrazole-based photoswitches and conducted a comparative study with 33 phenylazopyrazoles, comparing their photoswitching properties and the impact of electronic effects. Using UV–vis and NMR spectroscopy, we discovered that simple acylation of the pyrazole moiety leads to increased quantum yields of isomerization, long Z-isomer life-times, good spectral separation, and high photostability.
Keywords: azobenzenes; azopyrazoles; photochromism; photoswitches; substituent effects